Quality forming patterns in the cupcake enriched with pumpkin slices - Liubych, Vitalii; Novikov, Volodymyr; Zheliezna, Valeriia; Makarchuk, Marina; Balabak, Oleksandr; Kirian, Viktor; Bardakov, Volodymyr; Kyrpa, Mykola; Moskalets, Valentyn; Moskalets, Tetiana (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study into the effect of different quantities and shapes of fresh pumpkin slices on the technological properties of the cupcake. A comparative analysis of the technological properties of the cupcake with the addition of different quantities and shapes of pumpkin slices has been carried out. A change in the technological properties of the cupcake depending on the volume of pumpkin slices has been established. The use of fresh pumpkin slices reliably improves shrinkage during baking, humidity, and acidity of the cupcake. The volume of the cupcake is significantly reduced in this case. Porosity is significantly impaired when adding 30‒50 % of slices. The slice shape does not significantly affect the technological parameters of the cupcake. Social research was conducted; the main priorities for buyers of flour confectionery products were established. It is proved that the greatest importance when choosing food by consumers is given to the physical appearance of the finished product. Based on the research, it was found that in the technology of cupcake production, it is optimal to add 5‒25 % of fresh pumpkin slices of different shapes by weight of the dough. Applying this volume of slices makes it possible to bake a cupcake with a porosity of 9 points, a shrinkage at baking of 6.9–8.5 %, humidity of 6.9–12.8 %, a volume of 176–203 cm3, the acidity of 1.5–1.7 degrees. In addition, it is possible to use 30‒35 % of pumpkin slices. The porosity of a cupcake with such a formulation is at the level of 6.5–8.0 points. The cupcake quality meets the requirements set out by DSTU 4505:2005 and ISO 22000:2018. The difference from the conventional technique of utilizing non-traditional raw materials is the use of different quantities and shapes of fresh pumpkin slices. The use of pumpkin slices makes it possible to reduce the volume of dough in the finished product. The devised recommendations could be used by low-productivity grain processing enterprises when making flour confectionery products